The Role of miR-330-3p/PKC-α Signaling Pathway in Low-Dose Endothelial-Monocyte Activating Polypeptide-II Increasing the Permeability of Blood-Tumor Barrier - Liu, Jiahui; Liu, Libo; Chao, Shuo; Liu, Yunhui; Liu, Xiaobai; Zheng, Jian; Chen, Jiajia; Gong, Wei; Teng, Hao; Li, Zhen; Wang, Ping; Xue, Yixue (Frontiers in Cellular Neuroscience, 2017)
This study was performed to determine whether EMAP II increases the permeability of the blood–tumor barrier (BTB) by affecting the expression of miR-330-3p as well as its possible mechanisms. We determined the over-expression of miR-330-3p in glioma microvascular endothelial cells (GECs) by Real-time PCR. EMAP-II significantly decreased the expression of miR-330-3p in GECs. Pre-miR-330-3p markedly decreased the permeability of BTB and increased the expression of tight junction related proteins ZO-1, occludin and claudin-5, however, anti-miR-330-3p had the opposite effects. Anti-miR-330-3p could enhance the effect of EMAP-II on increasing the permeability of BTB, however, pre-miR-330-3p partly reversed the effect of EMAP-II on that. Similarly, anti-miR-330-3p improved the effects of EMAP-II on increasing the expression levels of PKC-α and p-PKC-α in GECs and pre-miR-330-3p partly reversed the effects. MiR-330-3p could target bind to the 3’UTR of PKC-α. The results of in vivo experiments were similar to those of in vitro experiments. These suggested that EMAP-II could increase the permeability of BTB through inhibiting miR-330-3p which target negative regulation of PKC-α. Pre-miR-330-3p and PKC-α inhibitor decreased the BTB permeability and up-regulated the expression levels of ZO-1, occludin and claudin-5 while anti-miR-330-3p and PKC-α activator brought the reverse effects. Compared with EMAP-II, anti-miR-330-3p and PKC-α activator alone, the combination of the three combinations significantly increased the BTB permeability. EMAP-II combined with anti-miR-330-3p and PKCα activator could enhance the DOX’s effects on inhibiting the cell viabilities and increasing the apoptosis of U87 glioma cells. Our studies suggest that low-dose EMAP-II up-regulates the expression of PKC-α and increases the activity of PKC-α by inhibiting the expression of miR-330-3p, reduces the expression of ZO-1, occludin and claudin-5, and thereby increasing the permeability of BTB. The results can provide a new strategy for the comprehensive treatment of glioma.